2014
DOI: 10.1161/strokeaha.114.006167
|View full text |Cite
|
Sign up to set email alerts
|

Novel Factor Xa Inhibitor for the Treatment of Cerebral Venous and Sinus Thrombosis

Abstract: Background and Purpose— Thrombosis of cerebral veins and sinus (cerebral venous thrombosis) is a rare stroke pathogenesis. Pharmaceutical treatment is restricted to heparin and oral anticoagulation with vitamin K antagonists (VKAs). Methods— Between January 2012 and December 2013, we recorded data from our patients with cerebral venous thrombosis. The modified Rankin scale was used to assess clinical severity; excellent outcome was defined as modified R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
85
4
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 4 publications
(1 reference statement)
12
85
4
4
Order By: Relevance
“…Recanalization rates and clinical outcome of our small sample of patients treated with rivaroxabam confirm previous observations [4,5], eventough these studies have retrospective, uncontrolled design and a small sample size, they all showed a similar clinical benefit in addition to NOAC better safety profile.…”
Section: Resultssupporting
confidence: 88%
“…Recanalization rates and clinical outcome of our small sample of patients treated with rivaroxabam confirm previous observations [4,5], eventough these studies have retrospective, uncontrolled design and a small sample size, they all showed a similar clinical benefit in addition to NOAC better safety profile.…”
Section: Resultssupporting
confidence: 88%
“…In about 20% of cases patients did not achieve reperfusion; however, in all instances, this was deemed related to old age or non-modifiable risk factors such as cancer and lupus [7]. The second study evaluated the use of rivaroxaban in the acute treatment of CVT and found no significant recurrences or complications during 8 months of follow-up [8].…”
Section: Discussionmentioning
confidence: 99%
“…There have been some case reports of cerebral sinus thrombosis being treated with dabigatran, rivaroxaban or edoxaban [7][8][9][10]. However, none of these case reports were randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%